Controller design of a wireless power transfer system - She, Zihao (2019)
Wireless Power Transfer (WPT) Technology has played a more and more important role in our production and life recently. It attracts peoples’ attention by its own advantages like safe and convenience. This project mainly focuses on the magnetically coupled resonant (MCR) WPT technology, based on inductive coupling fundamentals, which enables the WPT system to work efficiently with a low coupling coefficient. Nevertheless, most studies focus on open-loop WPT systems, which could not achieve good control functions. For better regulating the system output, a closed-loop control method is studied in the project. In addition, measures are also put forward to solve the problem of communication delay. On both the transmitter and receiver sides, the WPT system adopts full-bridge converters, each of which is made of four gallium-nitride (GaN) high- electron-mobility transistors (HEMTs) with the same parameters. Pulse density modulation (PDM) technique is used to control their respective on-off and realize the functions of inversion and rectification on the two sides respectively. A proportional-integral (PI) controller is used for the output regulation. Furthermore, since most of the existing WPT system dynamical models are 5th- or 9th-order models with complicated forms, this project uses a more simplified 3th-order model under tuned resonance condition for the dynamical analysis and controller design. All designs and analysis of the system are based on the MATLAB/Simulink simulation platform. The results are validated on a real experimental WPT platform.